エアロゾルゾンデとライダーで観測された北極成層圏エアロゾルの微物理特性と輸送過程の関係について - 白石, 浩一; 林, 政彦; 柴田, 隆; 藤原, 玄夫; 岩坂, 泰信; 中島, 英彰; 村田, 功; Shiraishi, Koichi; Hayashi, Masahiko; Shibata, Takashi; Fujiwara, Motowo; Iwasaka, Yasunobu; et al. (2014)
conference object